Mechanisms of chorioamnionitis‐associated preterm birth: interleukin‐1β inhibits progesterone receptor expression in decidual cells. Issue 4 (19th August 2015) - Guzeloglu‐Kayisli, Ozlem; Kayisli, Umit A; Semerci, Nihan; Basar, Murat; Buchwalder, Lynn F; Buhimschi, Catalin S; Buhimschi, Irina A; Arcuri, Felice; Larsen, Kellie; Huang, Joseph S; Schatz, Frederick; Lockwood, Charles J
Abstract: In chorioamnionitis (CAM), a major cause of preterm birth (PTB), maternal–fetal inflammation of the decidua and amniochorion cause the release of cytokines that elicit cervical ripening, fetal membrane rupture and myometrial activation. We posit that this inflammatory milieu triggers PTB by inhibiting progesterone receptor (PR) expression and increasing decidual prostaglandin (PG) production. Immunohistochemical staining of decidua detected significantly lower PR levels in decidual cells (DCs) from CAM‐complicated PTB. Incubation of DCs with IL‐1β decreased PR expression and significantly increased PGE2 and PGF2α production and COX‐2 expression. The addition of PGF2α to DC cultures also suppressed PR expression. However, the COX inhibitor, indomethacin, did not reverse IL‐1β suppression of PR expression in DC cultures. Although IL‐1β treatment activated the NF‐K B, ERK1/2 and p38 MAPK signalling cascades in DCs, inhibition of ERK1/2 MAPK signalling alone was sufficient to completely reverse the suppression of PR levels by IL‐1β. These findings suggest that CAM‐associated PTB is induced at least in part by IL‐1β‐mediated functional progesterone withdrawal. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.